The Role of Green Innovation Capabilities on The Relationship Between Total Quality Management And Sustainability Performance of Small And Medium Manufacturing Industry In Surabaya - Diharjo, Djojo; Watti, Risa; Azizah, Nurul (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the structural relationship between Total Quality Management (TQM) and corporate sustainability performance, with green innovation capabilities as a mediating variable, in the manufacturing industry of Small and Medium Enterprises (SMEs) in Surabaya. This study emphasizes the importance of TQM implementation and green innovation capabilities in driving organizational sustainability practices. The research method uses Structural Equation Modeling–Partial Least Squares (SEM-PLS). TQM is measured across four dimensions: product control management, process control management, vendor quality management, and customer relationship improvement. Corporate sustainability performance is measured through three dimensions, namely environmental, economic, and social sustainability, while green innovation capabilities are measured through green product innovation and green process innovation. The results show that TQM practices directly influence corporate sustainability performance across all dimensions and act as an antecedent of green innovation capabilities. Furthermore, green innovation capabilities are shown to mediate the relationship between TQM practices and corporate sustainability performance at both the construct and dimension levels. These findings indicate that TQM can be a holistic approach in improving the sustainability of small and medium industrial companies and building an innovative culture that encourages the creation of a circular social economy.